Viewpoints of the New York times’ editorials on Barack Obama’s power: 2008 - 2010 - Trương, Thị Cẩm Lê (2020)
Although the 44th U.S. black President – Barack Obama has been a rich controversial topic in many studies, such no work has analyzed his power on the related editorials of the New York Times. In response to this fact, a study on ―Viewpoints of the New York Times‘ Editorials on Barack Obama‘s Power: 2008-2010‖ has initiated, carried out and completed. The study has been an attempt to find out how the papers of New York Times viewed Barack Obama‘s power from the 2008 U.S. Presidential Election Day up to the mid-2010. Textual analysis was employed as the method used to analyze the Times‘ 173 editorials in the period of 2008-2010. The analysis examined the editorials about Obama‘s power based on four main categories: foreign policies, economy, politics and social issues. It had been found that under the eyes of the Times, Barack Obama‘s power into the four main areas had boldly changed between the first year and the first half of the second year. In addition, negative attitudes toward Barack Obama‘s administrating were nearly more prominent than the positives, especially in 2010. By offering thorough analysis on the papers of the Times, this research is expected to be a useful reference for teachers and students who take interested in the subject matter